Know where to go: evidence from a controlled trial of a healthcare system information intervention among immigrants - Signe Smith Jervelund; Thomas Maltesen; Camilla Lawaetz Wimmelmann; Jørgen Holm Petersen; Allan Krasnik (BMC, 2018)
Abstract Background Immigrants may face problems with accessing the Danish healthcare system due to, for example, lack of knowledge of how to navigate it, which may cause inappropriate healthcare-seeking. Danish municipalities provide a mandatory introduction and language programme for newly arrived immigrants, but no information on the healthcare system is offered. This study investigated what effects information about the Danish healthcare system may have on the hypothetical healthcare-seeking behaviour of newly arrived immigrants and their actual healthcare use. Methods A prospective intervention study of 1572 adult immigrants attending two language schools in Copenhagen was carried out. Two intervention groups received either a course or written information on the Danish healthcare system, respectively, while the control group received neither. Survey data included three case vignettes on healthcare-seeking behaviour (flu-like symptoms, chest pain and depression) and were linked to registry data on sociodemographic characteristics and healthcare use in the year to follow. Logistic regression and binomial regression analyses were performed. Results Appropriate hypothetical healthcare-seeking behaviour was reported by 61.8-78.8% depending on the vignette. Written information showed no effect on immigrants' hypothetical healthcare-seeking behaviour, while the course showed a positive effect on hypothetical healthcare-seeking behaviour for flu-like symptoms (adjusted odds ratio [AOR] = 1.71, 95% confidence interval [CI] = 1.01-2.91, p-value = 0.0467), but not on chest pain or depression. The interventions did not affect immigrants' actual healthcare use; all groups made lower use of health care services in the following year compared with the year where the study took place, except for the use of dental care which remained stable. Conclusions Information on the healthcare system embedded in the language school programme has the potential to facilitate immigrants' access to healthcare. Yet, the results underscore the need for further refinement and development of educational interventions, as well as ensuring adequate utilisation of healthcare services by other means. Multi-dimensional and multi-sectional efforts are important for integration issues within healthcare in Europe. Trial registration Health-seeking behaviour among newly arrived immigrants in Denmark ISRCTN24905314, May 1, 2015 (Retrospectively registered).